Promoting Entrepreneurial Orientation for Sustainability: The Roles of Self-Uncertainty and Fear of Failure - Ogunleye, Adedeji J. Ogunleye; Agesin, Bamikole E. Agesin; Popoola, Abiola O. Popoola (African Journal of Stability and Development (AJSD), 2025)
Nigeria is presently ravaged by banditry, terrorism, and kidnapping for ransom. These are crimes predominantly perpetrated by agile young and middle-aged individuals who ought to be actively engaged in entrepreneurship. Recognising the consequences of such societal breakdowns, United Nations member states convened in 2015 and developed an action plan— the 2030 Agenda for Sustainable Development— aimed at transforming the world through poverty and unemployment reduction, thereby promoting peace, social justice, and prosperity. A key component of this agenda is fostering entrepreneurial activity. However, existing evidence suggests that many individuals remain averse to these growth-oriented initiatives. Therefore, this study seeks to find out whether fear of failure and self-uncertainty are predictors of entrepreneurial orientation, using a total of 231 randomly selected residents of Ado-Ekiti metropolis. The respondents are 129 (55.8%) males and 102 (44.2%) females whose ages range from 18 to 70 years, with a mean age of 33.43 years. Standardised measures of fear of failure, self-uncertainty, and entrepreneurial orientation were used, and findings revealed that Fear of Failure and Self-Uncertainty, and their dimensions, are significant factors which predict entrepreneurial orientation. It is only the personal ability dimension of fear of failure that did not significantly predict entrepreneurial orientation. However, the dimension is negatively related, just as the potential of idea dimension, to entrepreneurial orientation, suggesting that as an individual’s fear of failure in relation to her/his perceived ability to succeed increases, her/his inclination towards entrepreneurial behaviours will decrease. The findings were discussed in light of available literature, and it is recommended that efforts must be geared towards tackling security challenges in Nigeria, in particular, and the developing countries in general, to address the fear-driven factors of funding and security which often over-ride confidence in prospective entrepreneurs’ skills, especially in volatile economies.